Striden mellem Grundtvig og H. C. Ørsted - Jessen, Erland (Grundtvig-studier, 1971)
The Controversy between Grundtvig and H. C. Ørsted 1814 - 15 By Erland Jessen The romantic period in Denmark offers numerous controversies, in which the ideological foundations of the period were held up for examination. In 1800 Schelling, The German philosopher, had given the final description of his cintellectualist’ philosophy in the work, System des transcendentalen Idealismus, and in Steffens’ ‘ Indledning til philosophiske Forelæsninger’ ( 1803) this all embracing romantic philosophy was introduced into Denmark.The clash between Grundtvig and H. G. Ørsted is the first general settlement with this ideology. Both combatants claimed to be Christians and convinced that Christianity was the true religion, but their interpretations of it were vastly different. Their fundamental disagreement was concerned with the governing principle of the universe, the nature of God. To Grundtvig the divine, in agreement with the biblical opinion, God was transcentental, whereas, in his urge towards a unification of the multiplicity of natural phenomena, Ørsted the scientist held the opinion of Spinoza and Plotin, further developed by Schelling, that God is immanent, identical with nature and matter. Fundamental disagreement about this governing principle of the world gave rise to conflicts within philosophy and science. The most important documents of the controversy were Ørsted’s Tmod den store Anklager’ and Grundtvig’s Tmod den lille Anklager’, whereby it is indicated that the controversy had the character of a legal dispute.Ørsteds criticism against Grundtvig is first and foremost directed against his ‘ Kort Begreb af Verdens Krønike i Sammenhæng’ ( 1812 ), in which Grundtvig, referring to the Bible, had pronounced severely upon peoples, individuals, sciences, and periods, thus for instance on Schelling, and such sciences as chemistry, astronomy, and mathematics. In great detail Ørsted defends romantic philosophy of nature against Grundtvig’s accusations, and he altogether refuses to recognise his right to speak and pass judgment with divine authority. The relationship between science and religion should be one of harmony and relative independence. Therefore, unlike in the days of the Inquisition, the advocates of Christianity should not be entitled to expurgate scientific results and decide on the choice of proper objects of study. According to Ørsted both religion and science are expressions of man’s striving towards God; in religion as an idea of constant harmony, in science as a confirmation of that idea.Grundtvig’s answer points to the Bible as the touchstone in all things human. Based on the Bible as they are, his condemnations cannot be regarded as an attempt to exalt himself at the expence of others, but as the ideal demands of religion on an age where the Commandments of the Bible are being evaded. He is extremely thorough-going in his settlement with Schelling. According to Grundtvig the harmony between the perceptual world and the reality of reason that had been described by Schelling and defended by Ørsted is incompatible with the words of the Bible. It veils the distinction between good and evil, God and man, Heaven and earth. To Grundtvig the universe is essentially of a dual nature, split up in a transcendental and a real world. Schelling’s denial of this duality, of the boundary between the transcendental and the real world, then, implies that this philosophy is atheistic, allied with the nature of evil. According to Grundtvig any scientific enterprise should yield to God’s supremacy. Religion indicates the goals that science may pursue, and any scientific research without religious anchorage is a bad thing.Throughout the controversy both Grundtvig and Ørsted stubbornly stuck to their own interpretations of the universe, the interpretations that later Brandes was to argue against in Det moderne Gennembruds Mænd ( 1883), when he stated his standpoint ‘within universal nature and not supernatural dogmatism5. By then, time had found new world views.